Association between functional tooth units and chewing ability in older adults: a systematic review. (22nd November 2012) - Naka, Olga; Anastassiadou, Vassiliki; Pissiotis, Argirios
<x xml:space="preserve">Abstract</x> Objectives To systematically review the current evidence on the relationship between dentition status and chewing ability in older adults, as the latter was subjectively perceived by questionnaires. Background Tooth loss is associated with functional impairment regarding chewing ability, depending on the number and the location of the remaining teeth. Methods A search of the English literature was undertaken using the appropriate electronic databases and keywords in order to answer the question of this review. Independent extraction of the related articles was carried out by two authors using predefined eligibility criteria. Results Full‐text analysis was performed for 51 articles of possible relevance. Finally, data were extracted from 18 studies, published in 20 articles that met the inclusion criteria. Conclusions Although there was a conflict between the studies relevant to the number of functional tooth units needed to maintain adequate oral function, it was revealed that chewing ability was closely related to the number and distribution of teeth remaining. Treatment plan should focus on the preservation of the strategic parts of the dental arch that are critical for adequate oral function. Long‐term prospective studies, comprising well‐defined criteria, clinical variables, methods and utilising comprehensive questionnaires, should be preferred to obtain a clearer picture on the association between masticatory ability and functional tooth units.